Heterosis en progenies F₁ provenientes de cruzamientos recíprocos del progenitor FL-109-UTB con ocho cultivares de Arroz (Oryza sativa L. ssp. indica) - Castro Moreira, Aaron Moises (2019)
This research work was carried out at the Experimental Farm, "El Palmar" of the Technical University of Babahoyo, CEDEGE Project, province of Los Ríos, located at Km 12 of the Babahoyo - Montalvo road. This work was oriented to the study of the heterosis of F₁ populations in direct and reciprocal crosses of the FL-109 progenitor with eight rice cultivars. The objectives of this investigation were: To establish the heterotic vigor in segregating populations F1 deriva, derived from the parent FL-109-UTB, used as both male and female parental, in combination with eight parents and choose the progenies of better agronomic behavior and production, in terms of hybrid vigor. During the development of the investigation, all the agricultural work that rice cultivation demands, such as: soil analysis, soil preparation, planting, irrigation, fertilization, weed control and harvesting were carried out. The agronomic variables evaluated were: Vigor, Vegetative cycle (days), number of tillers per plant, number of panicles per plant, Flag leaf length (cm), Flag leaf width (cm), Plant height (cm), Panicle length (cm), Grains / panicle, Days to flowering, Sterility (%), Shelling (%), Yield (g / plant), Weight of 1000 grains (g), Length grain (mm), Width grain (mm) and Shape of the grain The different variables evaluated were statistically analyzed using central tendency measures (mean, mode), dispersion measures (variance and standard deviation). In addition, frequency distribution tables, histograms and / or frequency polygons were developed. In the variable vegetative vigor 87.5% of the progeny in studies; FL-109 / G112, FL-109 / BA-100, FL-109 / G-111, FL-109 / FI-107, FL-109 / G-113, FL-109 / FI-106, FL-109 / CA-102, G-112 / FL-109, BA-100 / FL-109, FI-107 / FL-109, G-113 / FL-109, FI-105 / FL-109, FI-106 / FL- 109, CA-102 / FL-109, were very vigorous. In the variable yield grams per plant according to the analysis of heterosis 81.25% of the populations under study (FL-109 / G-112, FL-109 / BA-100, FL-109 / G-111, FL-109 / G-113, FL-109 / FI-105, FL-109 / CA-102, G-112 / FL-109, BA-100 / FL-109, G-111 / FL-109, FI-107 / FL -109, G-113 / FL-109, FI-105 / FL-109, CA-102 / FL-109 outperform compared to their parents